Profit shifting of multinational corporations in the European Union: Evidence and policy reforms - Petr Janský (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Profit shifting of multinational corporations (MNCs) negatively affects citizens, governments as well as other companies in the European Union. This consensus seems to be emerging in spite of the fact that the phenomenon of profit shifting is unobservable directly and therefore only indirect and imperfect estimates can shed light on its effects. In this study, I rely on one set of such estimates, from an academic working paper by Garcia-Bernardo & Jansky (2021), to focus on its negative effects on the EU member states' government revenues. Two thirds (18 out of 27) of the EU member states lose out due to profit shifting of MNCs. At the same time, a few EU member states, most notably Netherlands, Ireland and Luxembourg, serve as tax havens and enable this tax avoidance. The EU as whole loses out due to profit shifting. When summed up across the EU member states, 302 billion USD (287 billion EUR) are shifted out of the EU yearly, while 215 billion USD (204 billion EUR) are shifted in. The difference is even starker when expressed in the estimated tax revenues: the EU is losing 12 billion USD (11 billion EUR) while gaining 53 billion USD (50 billion EUR). The bigger difference in estimated tax revenue than in profit shifting is due to the fact that, almost by definition, the shifted profits are taxed at a lower rate in their destination than if they were at their origin. For example, Cayman Islands tax shifted profits at zero rate, whereas profits would be taxed at higher rates in basically all countries from which they were shifted out. In corporate tax avoidance, losers lose more than winners win. Last, but not least, I discuss the global minimum tax rate reform proposals, discussed during 2021. Overall, tax avoidance and the reforms to counter it are, more often than not, the two sides of the same coin and why I draw five lessons jointly for both.
Keywords: F23; H25; H26; H32; 330; multinational corporation; corporate taxation; profit shifting; effective taxrate; country-by-country reporting; European Union